Mental Strain and Chronic Stress among University Students with Symptoms of Irritable Bowel Syndrome. (16th June 2013) - Gulewitsch, Marco D.; Enck, Paul; Schwille-Kiuntke, Juliane; Weimer, Katja; Schlarb, Angelika A.
Abstract : Aim . To investigate the degree of mental strain and chronic stress in a German community sample of students with IBS-like symptoms. Methods and Materials . Following an internet-based survey about stress, this study recruited 176 German university students (23.45 ± 2.48 years; 48.3% males) with IBS-like symptoms according to Rome III and 181 students without IBS (23.55 ± 2.82 years; 50.3% males) and compared them regarding current mental strain (SCL-90-R) and the extend of chronic stress. Beyond this, IBS subtypes, IBS severity, and health care utilization were assessed. Results . Students fulfilling IBS criteria showed significantly elevated values of mental strain and chronic stress. Nearly 40% of the IBS group (versus 20% of the controls) reached a clinically relevant value on the SCL-90-R global severity scale. IBS subtypes did not differ in terms of mental distress or chronic stress. Somatization, anxiety, and the chronic stressors "work overload, " "social tension, " and "dissatisfaction with job" were most closely connected to IBS symptom severity. Regarding health care utilization, our results show that consulting a physician frequently was not associated significantly with elevated mental strain or chronic stress but with IBS symptom severity. Conclusion . Our data contribute additional evidence to the distinct association between psychological stress and IBS in community samples.